Effect of stocking density on the perfonnance, carcass yield and meat composition of broiler chickens (2016)
Broiler chickens require adequate feed intake and uninterrupted emission of heat for intensive growth. An eight-week feeding trial was conducted to investigate the effects of stocking density on performance, carcass yield and meat composition of broilers. A total of 240 one-day old Arbor acre broiler chicks were randomly allocated to three stocking densities: Lower stocking density (LSD) of 10 birds/m2; Recommended stocking density (RSD) of 12 birds/m2; and Higher stocking density (HSD) of 14 birds/m2 respectively, with 4 replicates each having 20 birds per replicate. Feed and water were supplied ad libitum. Final live weight(FLW); Feed intake(FI); Feed conversion ratio(FCR); Mortality(%); Dressed weight(%); Prima cuts(%); Abdominal fat(%) and meat composition were assessed. Data were subjected to descriptive statistics and ANOVA °°=0.05. Birds on HSD had numerically higher FLW (2262.80 g), better FCR (2.08) that was similar to that of LSD (2.07) and significantly lower mortality (0.00%). The values of the prime cuts (thigh, drumstick and breast), abdominal fat and meat protein were similar between birds on LSD and HSD. Up to stocking density 14birds/m2 broiler chickens' performance and carcass characteristics were not negatively affected.